Frictionless Sharing and Digital Promiscuity - Payne, Robert (Communication and critical/cultural studies, 2014)
This article analyses the recent Facebook innovation of "frictionless sharing", a term which describes a smoother and wider distribution of content by individual users and a less overtly acknowledged but more efficient instrumentalization of users' immaterial labour within a structure of corporate monetization. It builds on my recent work on "the sharing subject" of contemporary digital media, in which I argue that current online social networking practices, in their emphasis on "sharing" content with networks of contacts, construct and validate the networked subject according to a version of neoliberal individualism. Moreover, the construction of this subject position implicitly recalls the heteronormativity of AIDS panic, through an unlikely rebranding of promiscuity as a desirable and successful mode of interactivity. If the new rhetoric of "sharing" erases the riskiness of circulation previously encoded in dominant images of virality, notably behaviours associated with HIV, then what is the relationship of the projected potential of "frictionless sharing" to existing normative frames of ethics and morality? In approaching this question, I revisit significant queer interventions into concepts of community and risk that emerged in the post-AIDS context, notably Tim Dean's recent examination of the barebacking subculture to which mediations of an idealized frictionlessness are also central.